Yatra - "Sibal, Nina" (New Delhi, 1987)
Midnight's Children was a fabulation of modern Indian history seen through the consciousness of a boy brought up in a Muslim family which came from Kashmir. Krishna Chahal of Yatra is brought up in a Sikh family that came originally from the North West Frontier Province
Keywords: Fiction